Incumbent-quality advantage and counterfactual electoral stagnation in the U.S. Senate - Ivan Pastine; Tuvana Pastine; Paul Redmond (University College Dublin, UCD School of Economics, 2012)
This paper presents a simple statistical exercise to provide a benchmark for the degree of electoral stagnation without direct officeholder benefits or challenger scare-off effects. Here electoral stagnation arises solely due to incumbent-quality advantage where the higher quality candidate wins the election. The simulation is calibrated using the observed drop-out rates in the U.S. Senate. From 1946 to 2010, the observed incumbent reelection rate is 81.7 percent; the benchmark with incumbent-quality advantage alone is able to generate a reelection rate of 78.2 percent. In the sub-sample from 1946 to 1978, the reelection rate from the simulation is almost identical to the observed. The rates diverge in the second part of the sub-sample from 1980 to 2010, possibly indicating an increase in electoral stagnation due to incumbency advantage arising for reasons other than incumbent-quality advantage.
Keywords: 330